Purification of laboratory chemicals - PERRIN, D D.; Armarego, W.L.F. ([S.l.] : Butterworth-Heinemann, 1997)
The purpose of this book is to help chemists, biochemists and other scientists purify the chemical reagents which they use in their work. Despite the fact that commercially available chemicals are often of a very high quality, and quite satisfactory for some applications within science and technology, it is becoming almost as important to know what impurities are present and make allowance for them as to remove them completely. This book will show you how. Chapter 1 has been reorganised and updated, and most of it is in smaller print in order not to increase the size of the book. Chapters 2 and 5 have been similarly altered and combined into one chapter, Chapter 2, again in order to save pages. 800 and 350 entries have been added to Chapter 3 (25% increase) and Chapter 4 (44% increase) respectively, and 400 entries (310% increase) were added to Chapter 5 (Chapter 6 in the third edition) making a total of 5700 entries, all resulting in an increase from 319 to 529 pages, i.e. ca 35%. This considerably expanded and revised fourth edition includes much new material dealing with modern reagents for natural products chemistry, protein biochemistry and molecular biology. It also includes many individual compounds not previously covered, and more information is given for most entries, including melting and boiling points, molecular weights, refractive indexes, densities and CAS registry numbers, as well as likely contaminants and storage conditions in appropriate cases.
Keywords: chemicals,laboratory chemicals,purification